The Growth of Vocational High School Students' 4C Skills on the Use of PjBL STEM-Based Physics Digital Module - Mugi Lestari; Supriyadi Supriyadi; Sulhadi Sulhadi (Physics Communication, 2023)
The Partnership for 21st Century Learning (P21) developed the Framework for 21st Century Learning to help education practitioners integrate skills into lesson teaching. This framework describes the skills, knowledge, and expertise that students must master in order to succeed in work and life. One of the skills that must be mastered by students in facing the 21st century is the 4C skill which consists of critical thinking, communication, collaboration, and creativity skills. This study aims to analyze the growth of the 4C skills of SMK students as the effect of implementing the use of PjBL STEM-based digital physics modules. This research is an experimental study with the before-after method, which compares the conditions before and after the implementation of learning activities. Data was collected by filling out a questionnaire with a Likert scale by students. The results showed that the 4C skills of vocational high school students grew significantly.